Subclinical intramammary infection does not affect bovine milk ethanol stability - Cristian Marlon de Magalhães Rodrigues Martins; Juliano Leonel Gonçalves; Bruna Gomes Alves; Marcos André Arcari; Marcos Veiga dos Santos (Brazilian Journal of Veterinary Research and Animal Science, 2018)
The present study hypothesized that intramammary infection (IMI) might reduce milk ethanol stability (MES), mainly when IMI is caused by major pathogens. Thus, this study evaluated the effect of IMI on bovine MES using a natural exposure experimental design. Ninety-four lactating cows from five dairy herds were selected once they were determined to have an IMI, based on milk bacteriological culturing with positive isolation and somatic cell count (SCC) > 200×103 cells/mL in two out of three composite milk samples collected during three consecutive weeks. After selection, cows were sampled a second time (within two weeks) for evaluation at mammary quarter level (n = 326): milk yield (kg/quarter/day), MES, composition (fat, protein, lactose, casein, total solids and solids-non-fat), and bacteriologic culture. The effect of subclinical mastitis on MES was tested by two models: 1) comparison of healthy vs. infected quarters; and 2) comparison of contralateral mammary quarter within cow. The only milk composition variable associated with MES was lactose (r = 0.18; P < 0.01). Subclinical IMI did not affect MES when the comparison was performed using both models (1 and 2). Likewise, MES did not change when infected quarters were sorted into two groups of pathogens (major, minor and infrequent; and contagious, environmental, minor and infrequent) and compared with healthy mammary quarters. Considering the results of both models, subclinical IMI did not affect MES of dairy cows.